PreS/2-21-Guided siRNA Nanoparticles Target to Inhibit Hepatitis B Virus Infection and Replication - Gao, Lixia; Yang, Jie; Feng, Jutao; Liu, Ziying; Dong, Ying; Luo, Jiangyan; Yu, Liangzhentian; Wang, Jiamei; Fan, Hongying; Ma, Weifeng; Liu, Tiancai (Frontiers in Immunology, 2022)
A viable therapy is needed to overcome the deadlock of the incurable chronic hepatitis B (CHB). The prolonged existence of covalently closed circular DNA (cccDNA) and integrated HBV DNA in the nucleus of hepatocytes is the root cause of CHB. As a result, it is critical to successfully suppress HBV DNA replication and eliminate cccDNA. RNA interference has been proven in recent research to silence the expression of target genes and thereby decrease HBV replication. However, siRNA is susceptible to be degraded by RNA enzymes in vivo, making it difficult to deliver successfully and lacking of tissue targeting. To exploit the advantages of siRNA technology while also overcoming its limitations, we designed a new strategy and prepared biomimetic nanoparticles that were directed by PreS/2-21 peptides and precisely loaded HBV siRNA. Experiments on these nanoparticles in vitro and in vivo revealed that they are tiny, stable, safe and highly targetable, with high inhibitory effects on HBV DNA, pgRNA, cccDNA, HBeAg and HBsAg. PreS/2-21-directed nanoparticles loaded with HBV gene therapy drugs are expected to be promising for the treatment of CHB.